THE EFFECT OF JOB STRESS AND FINANCIAL COMPENSATION TOWARD OCB AND EMPLOYEE PERFORMANCE: (Case Study in PT. MENTARI SEJATI PERKASA Private Companies in Surabaya) - Enny Istanti; Bramastyo Kusumo Negoro; Achmad Daengs GS (STIE Mahardhika, 2021)
The study analyzes the after effect of job stress and financial compensation both OCB and OCB to performance. This research uses explanatory type with a quantitative approach. Data collection techniques in this study were carried out by means of a literature study. Data analysis technique used is the Structural Equation Model (SEM) with the Smart Partial Least Square (PLS) tool. Results of this study shows that: (1) Job stress does not has a significant effect on OCB; (2) Financial compensation has a significant effect on OCB; (3) OCB has a significant effect on employee performance.